Sociodemographic Factors and Health Insurance Coverage Are Associated with Invasive Breast Cancer in Tennessee: Appalachian and Non-Appalachian County Comparison - Faustine Williams; Lohuwa Mamudu; Charlotte J. Talham; Francisco A. Montiel Ishino; Martin Whiteside (Mary Ann Liebert, 2022)
Background: Tennessean women experience the 12th highest breast cancer (BC) mortality in the United States. Yet, few studies have examined BC outcomes among Tennessean women in and outside of Appalachia. We examined whether sociodemographic factors and health insurance status were associated with invasive BC in Tennessee by Appalachian and non-Appalachian county designation. Materials and Methods: Using the Tennessee Cancer Registry, we identified 52,187 women, aged ?18, diagnosed with BC between 2005 and 2015. Multivariable logistic regression was performed to examine associations between invasive BC and sociodemographic characteristics, health insurance coverage, and county designation (Appalachian/non-Appalachian). Regression analyses stratified by county designation were subsequently performed. Results: In Tennessee, younger women had lower odds of invasive BC diagnosis (<45: odds ratio [OR]?=?0.74, 95% confidence interval [CI]?=?0.67?0.81; 55?64: OR?=?0.91, 95% CI?=?0.84?0.97) compared to women ?65. Married Tennessean women had 12% (95% CI?=?1.04?1.21) higher odds of invasive BC than single women. Further, both public (OR?=?1.81, 95% CI?=?1.41?2.33) and private (OR?=?1.36, 95% CI?=?1.06?1.76) health insurance were found to increase odds of invasive BC compared to no insurance/self-pay. Results from the subpopulation analyses were largely consistent with overall findings. In Appalachian counties, women on public health insurance had increased odds (OR?=?1.42, 95% CI?=?1.00?2.03) of invasive BC compared to uninsured/self-pay women, while in non-Appalachian counties, women insured both publicly (OR?=?2.25, 95% CI?=?1.57?3.24) and privately (OR?=?1.68, 95% CI?=?1.16?2.24) had increased odds of invasive BC. Conclusions: The results identify risk factors for Tennessean women in Appalachian and non-Appalachian counties whose malignancies evaded early detection, increasing risk of mortality.